RNAi-Based Approaches for Pancreatic Cancer Therapy - Kim, Min Ju; Chang, Hyeyoun; Nam, Gihoon; Ko, Youngji; Kim, Sun Hwa; Roberts, Thomas M.; Ryu, Ju Hee (MDPI, 2021)
Pancreatic cancer is one of the most lethal forms of cancer, predicted to be the second leading cause of cancer-associated death by 2025. Despite intensive research for effective treatment strategies and novel anticancer drugs over the past decade, the overall patient survival rate remains low. RNA interference (RNAi) is capable of interfering with expression of specific genes and has emerged as a promising approach for pancreatic cancer because genetic aberrations and dysregulated signaling are the drivers for tumor formation and the stromal barrier to conventional therapy. Despite its therapeutic potential, RNA-based drugs have remaining hurdles such as poor tumor delivery and susceptibility to serum degradation, which could be overcome with the incorporation of nanocarriers for clinical applications. Here we summarize the use of small interfering RNA (siRNA) and microRNA (miRNA) in pancreatic cancer therapy in preclinical reports with approaches for targeting either the tumor or tumor microenvironment (TME) using various types of nanocarriers. In these studies, inhibition of oncogene expression and induction of a tumor suppressive response in cancer cells and surrounding immune cells in TME exhibited a strong anticancer effect in pancreatic cancer models. The review discusses the remaining challenges and prospective strategies suggesting the potential of RNAi-based therapeutics for pancreatic cancer.
Keywords: SMALL INTERFERING RNA; TUMOR-ASSOCIATED MACROPHAGES; SIRNA DELIVERY; STELLATE CELLS; DRUG-DELIVERY; CO-DELIVERY; INTRACELLULAR TRAFFICKING; EXTRACELLULAR VESICLES; ENHANCED PERMEABILITY; LIPID NANOPARTICLES